Synthesis and optical properties of CdS quantum dots via paraffin liquid and oleic acid - Sadeq, Zainab S. (Iraqi Journal of Physics, 2019)
In this study, an easy, low-cost, green, and environmentallyfriendlier reagents have been used to prepare CdS QDs, in chemicalreaction method by mixed different ratio of CdO and sulfur inparaffin liquid as solvent and oleic acid as the reacting media indifferent concentration to get the optimum condition of the reactionto formation CdS QDs. The results give an indication that thebehavior is at small concentration of 4ml of the oleic acid is bestconcentration which give CdS QDs of small about to 9.23 nm withnano fiber configuration.